2020
DOI: 10.1038/s41598-020-67642-x
|View full text |Cite
|
Sign up to set email alerts
|

The Great Acceleration of fragrances and PAHs archived in an ice core from Elbrus, Caucasus

Abstract: the Great Acceleration of the anthropogenic impact on the earth system is marked by the ubiquitous distribution of anthropogenic materials throughout the global environment, including technofossils, radionuclides and the exponential increases of methane and carbon dioxide concentrations. However, personal care products as direct tracers of human domestic habits are often overlooked. Here, we present the first research combining fragrances, as novel personal care products, and polycyclic aromatic hydrocarbons (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 57 publications
1
11
0
2
Order By: Relevance
“…By contrast, the Ant/(Ant + Phe) ratio suggests a petrogenic origin, as it was < 0.10 across all six samples from July and four samples from September 2019. Similar results were obtained by Vecchiato et al (2020), who explained this apparent contradiction in contamination origin with the different reactivities of the isomers during their atmospheric transport and aging processes.…”
Section: Origin Of Pah Contaminationsupporting
confidence: 86%
See 2 more Smart Citations
“…By contrast, the Ant/(Ant + Phe) ratio suggests a petrogenic origin, as it was < 0.10 across all six samples from July and four samples from September 2019. Similar results were obtained by Vecchiato et al (2020), who explained this apparent contradiction in contamination origin with the different reactivities of the isomers during their atmospheric transport and aging processes.…”
Section: Origin Of Pah Contaminationsupporting
confidence: 86%
“…High values were reported by Hu et al (2012), who recorded mean HHCB and AHTN concentrations of 11.0 and 33.3 ng/L, respectively, in snow samples from the Beijing urban area. Fragrances have also been detected in surface snow at Svalbard (Vecchiato et al, 2018), with concentrations up to 72 ng/L, and these compounds have been monitored for the first time in the Elbro ice core (Vecchiato et al, 2020), where an increase in concentration from 1930 to 2005 was reported.…”
Section: Synthetic Fragrancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, these results remain of interest because, according to their persistence observed for other POPs and banned pesticides, CPF will continue to be detected in the environment for several years, similar to endosulfan [63]. In addition, these findings may be valid for other lipophilic and semi-volatile toxicants that may be found in remote areas, such as the synthetic fragrances or the polycyclic aromatic hydrocarbons [7,64]. This study emphasises the importance of considering effects on behaviour (e.g., swimming speed) in early detection of the adverse effects of any stressor in toxicology evaluations and the incipient need to use wild alpine species for the evaluation of natural ecosystems to increase the ecological realism of ex situ experiments.…”
Section: Discussionmentioning
confidence: 98%
“…Last, considering that a fundamental step between sample collection and analysis is ensuring analyte preservation and preventing or minimizing any physical or chemical change (e.g., adsorption, diffusion, volatilization, oxidation, and microbial degradation), we assessed organic tracer preservation after melting of the ice/snow samples. We investigated two main sample storage strategies that involve the re-freezing of previously molten ice samples and the physical adsorption on a solid phase . Previous studies performed on different chemicals (drugs) and matrices (wastewater) showed divergent results, , indicating that case-specific investigations are needed to assess analyte’s preservation during sample storage.…”
Section: Introductionmentioning
confidence: 99%